Making Sense of Dei Verbum : Moslem Reflections on The Relation Between Scripture and Tradition - Ali, Muhammad Modassir (DINIKA : Academic Journal of Islamic Studies, 2016)
Like all great religions of the world, Christianity is a religion steeped in revelation. It tries to convince its followers that it was through the process of revelation that God made Himself known both in the Old and New Testaments, climaxing in the saving action of Jesus Christ. Although this is the starting point of Christian revelation, it would surprise many to know that it was only in the last five centuries that Christians started debating the issue and nature of revelation. In the present article, we shall critically examine how Catholic Christians started perceiving the notion of revelation from the Second Vatican Council (1962-1965) as enshrined in the Constitution Dei Verbum of the Council and the issues that keep Catholics engaged with regard to it with particular focus upon the relation between Scripture and Tradition and the ensuing tensions.